Efficacy of postoperative aspirin administration for improving survival of microvascular free flaps in head and neck reconstruction procedures: A systematic review - Anu Jose; Nitin Bhola; Anchal Agarwal (Oral Oncology Reports)
Background: Reconstruction of head and neck defects following ablative surgery using Microvascular flaps has become the golden standard in the modern era. Though the results and success rate given by reconstruction using Microvascular free flaps is fascinating, flap failures are commonly encountered. Multiple intraoperative and postoperative parameters were defined in the literature as the reason for flap failures, the most common being venous thrombosis. Objectives: The objective of this study is to define the efficacy of administering aspirin postoperatively for improving flap survival outcomes. Data sources: A comprehensive and systematic search using the PRISMA guidelines was done to identify literature evidence related to administration of aspirin for improvement in flap survival outcome following Microvascular surgeries. This search was conducted using the following Medical Subject Headings (MeSH) terms: phrases “Postoperative aspirin,” “Postoperative antiplatelet,” and “microvascular thrombosis”. Results: The literature search resulted in a total of 69 study articles, of which five publications were used in the present review, according to a selection based on the pre-established eligibility criteria. The review showed that with the use of aspirin flap failure owing to thrombosis formation is less than 5 %. Discussion: This systematic literature review showed that Flap failure rate due to arterial or venous thrombosis is acceptable that is less than 5 % with the use of aspirin as a antitplatelet agent in postoperative period following Microvascular surgeries. However the number of studies using aspirin as a single agent in postoperative period is less to arrive at a definitive conclusion.